PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. TRANSCO ENERGI UTAMA POM - Putri, Nova Mulia; Zusmawati, Zusmawati (Ensiklopedia of Journal, 2025)
Abstract: The objective of this research is to determine the effect of compensation     and motivation on employee performance at PT. Transco Energi Utama POM. This study is a descriptive quantitative research. The research was conducted at PT. Transco Energi Utama POM, located in Nagari Tigo Sungai, Pancung Soal District, Pesisir Selatan Regency. The data analysis technique used in this research is SPSS. The sample consisted of 92 individuals, selected using probability sampling methods. Data collection was carried out using questionnaires and documentation methods. The results of this study indicate that both compensation and motivation have a positive and significant effect on employee performance.Keywords: Compensation, Work Motivation and Performance.